2018
DOI: 10.1186/s12917-018-1419-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple midline defects identified in a litter of golden retrievers following gestational administration of prednisone and doxycycline: a case series

Abstract: BackgroundThe teratogenic effects of immunomodulatory and certain antimicrobial therapies are described in small rodents and humans. While the described teratogenic effects in small rodents have been extrapolated to make conclusions about its use in the pregnant dam, teratogenic effects of prednisone and doxycycline have not yet been reported in the dog. Here we report and describe midline defects observed in a litter of golden retriever puppies exposed to mid-gestational immunosuppressive and antimicrobial th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Recently, in veterinary literature, liver malformation due to diaphragmatic hernia was reported in puppies whose mother was under doxycycline, prednisone and tramadol administration (Kaplan et al, 2018). However, no similar information was observed in this case.…”
Section: Introductionmentioning
confidence: 64%
“…Recently, in veterinary literature, liver malformation due to diaphragmatic hernia was reported in puppies whose mother was under doxycycline, prednisone and tramadol administration (Kaplan et al, 2018). However, no similar information was observed in this case.…”
Section: Introductionmentioning
confidence: 64%
“…Cantrell’s syndrome or pentalogy have been well described in humans, with an estimated prevalence between 1:65 000 and 1:200 000,2 whereas, to the authors’ knowledge, an incomplete form of the syndrome has been reported in dogs and cats rarely3–10; a complete pentalogy has only been reported in one litter of puppies 11. Therefore, the true prevalence in animals is unknown due to the rare nature of this syndrome.…”
Section: Discussionmentioning
confidence: 83%
“…Eiger et al 10 used a titanium contourable mesh plate, as the age of the patient prevented primary closure. Other case reports did not address the sternal cleft 5 8 9…”
Section: Discussionmentioning
confidence: 99%
“…Animals with PPDH often have other concurrent congenital abnormalities such as midline defects (e.g., umbilical hernia, cleft palate, sternal abnormalities) and cardiac defects (e.g., ventricular septal defects, subaortic stenosis, pulmonic stenosis, atrial septal defect) (4)(5)(6)(7)(8). Peritoneopericardial diaphragmatic hernia is commonly seen as a congenital abnormality in several animals of the same litter (6)(7)(8)(9). Therefore, breeding of affected animals is not recommended, and screening of littermates for PPDH should be performed.…”
Section: Introductionmentioning
confidence: 99%